IMPLEMENTASI PENDIDIKAN KARAKTER DALAM KURIKULUM 2013 - Sri Harini (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2018)
Abstract The research is aime to analize the implementation of character education in applying The 2013 Curiculum a SMP Negeri 1 Sewon. This research used the qualitative method. The collecting data this research use many tecniques such as 1) interviews, 2) observations, 3) documents study. Data analysis techniques in the research is trianggulation data.This research implies that SMP Negeri 1 Sewon has implemented the character education by carrying out the teaching learning activietes and self development systematically, such 1) planning program related of the school mission and vision which is dones at the begaining of the year, 2) organizing, 3) implemented in self development and extracurricular activities and teaching learning activities as well, 4) monitoring and evaluating that is done the headmaster and all staff with the teachers supervisor. Keywords: implementation, character education, curriculum 2013